Audit-related attributes, regulatory reforms and timely disclosure: Further evidence from an emerging market. Issue 2 (3rd July 2017) - Samaha, Khaled; Khlif, Hichem
Abstract : Purpose: This paper aims to examine the impact of audit-related attributes and regulatory reforms on timely disclosure as proxied by audit report lag (ARL) in an emerging market setting, namely, Egypt. Design/methodology/approach: The paper used the balanced panel data of 372 firm-years observations of the most actively traded companies on the Egyptian Stock Exchange over the period from 2007 to 2010. The study measures the dependent variable of ARL as the number of days between the client's fiscal year-end and the audit report. Findings: Multivariate analysis indicates that audit committee activity (proxy for regulatory reforms) and external auditor type (proxy for audit-related attributes) contribute significantly to the reduction of ARL and increase disclosure timeliness. Furthermore, the paper found that ARL witnessed a slight decrease following the adoption of the new Egyptian Standards on Auditing (ESA). Finally, the paper's findings show that industry types moderate the relationship between ARL and several audit-related variables and corporate governance attributes. Practical implications: The results may have policy implications for both regulators and investors. For instance, policymakers in Egypt can enact new rules to reduce the Chief Executive Officer duality and establish the minimum required number of audit committee meetings to improve transparency level and, thus, increase disclosure timeliness. Besides, if future regulations aiming to increase disclosure timeliness are intended by Egyptian regulators, this paper's findings suggest that this may have implications for the audit market because the Big Four audit firms will be more able to meet shorter audit delays. Originality/value: The empirical evidence provided in this study further enhances the understanding of timely disclosure in Egypt which represents one of the leading emerging markets in the Middle East and North Africa region.